Comutations and KRASG12C inhibitor efficacy in advanced NSCLC - Negrao, Marcelo; Christopoulos, Petros; Stenzinger, Albrecht (Cancer discovery, 2023)
In this work, we identify co-occurring genomic alterations in KEAP1, SMARCA4, and CDKN2A as independent determinants of poor clinical outcomes with KRASG12Ci monotherapy in advanced NSCLC, and we propose a framework for patient stratification and treatment personalization based on the comutational status of individual tumors.
Im Titel erscheint die Zeichenfolge "G12C" hochgestellt
Gesehen am 15.11.2023